THE ROLE OF IL-10 IN BURN OUTCOME WITH AND WITHOUT SEPTIC - Lina A.Hassan; Ali A.Majeed; Mayyada F. Darweesh (Scholar Express Journals, 2022)
From December 2020 to November 2021, 60 patients entered the Al Sadder hospital in Al Najaf province, Iraq. The patients were divided into two groups: 40 with pseudomonas aeruginosa and 20 uninfected. The purpose of this study was to identify the function of the anti-inflammatory cytokine interleukin 10 (IL-10) in the pathophysiology of burn injuries. The patients were divided into two groups based on gender (34 males and 26 females) and age (1-61) years. To eliminate patients who had received antibiotic medication during the sample collection. There was a significant difference between males and females in this study, with the highest frequency of patient age being 16-30 (36.6 %), followed by 31-45 (30 %), 1-15 (23.4 %), and 46-61 (10%).All patients divided according to total degree of burn . However, P. aerogenosa antibiotic sensitivity test, in contrast most bacterial isolates exhibited high resistance to Ceftazidime (90%) Tobramycin (80%) and Gentamicin (80%), whereas resistance to Ciprofloxacin (50%) Amikacin (40%) and Pipracillin (70%) was variable finally less resist to TC (20%) and no resistance toward IMP (0 %). The study found that patients with P.aerogenosa infection had a substantially higher mean blood concentration of IL-10 (61.4 ± 11.8) than healthy controls (4.58 ± 0.77), whereas noninfected patients had a concentration of (18.21 ± 3.5 )pg/ml and non-infected patients had a concentration of (4.5 ± 0.06) pg/ml.
Keywords: burn sepsis; P. aerogenosa; antibiotic sensitivity; IL-10